Methodological quality of guidelines for management of Lyme neuroborreliosis. Issue 1 (December 2015) - Dersch, R.; Toews, I.; Sommer, H.; Rauer, S.; Meerpohl, J.
Abstract Background Many aspects of clinical management of Lyme neuroborreliosis are subject to intense debates. Guidelines show considerable variability in their recommendations, leading to divergent treatment regimes. The most pronounced differences in recommendations exist between guidelines from scientific societies and from patient advocacy groups. Assessment of the methodological quality of these contradictory guideline recommendations can be helpful for healthcare professionals. Methods Systematic searches were conducted in MEDLINE and databases of four international and national guideline organizations for guidelines on Lyme neuroborreliosis published from 1999–2014. Characteristics (e.g., year of publication, sponsoring organization) and key recommendations were extracted from each guideline. Two independent reviewers assessed the methodological quality of each guideline according to the Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool. AGREE II scores from guidelines developed by scientific societies and from patient advocacy groups were compared across domains. Results We identified eight eligible guidelines of whichn  = 6 were developed by scientific societies andn  = 2 by patient advocacy groups. Agreement on AGREE II scores was good (Cohen's weighted kappa = 0.87, 95 % CI 0.83–0.92). Three guidelines, all from scientific societies, had an overall quality score of ≥ 50 %. Two of them were recommended for use according to the AGREE II criteria. Across all guidelines, the AGREE II domain with the highest scores was "Clarity of Presentation" (65, SD 19 %); all other domains had scores < 50 % with the domain "Applicability" having the lowest scores (4, SD 4 %). Guidelines developed by scientific societies had statistically significantly higher scores regarding clarity of presentation than guidelines from patient advocacy groups (p  = 0.0151). No statistically significant differences were found in other domains. Conclusions Current guidelines on Lyme neuroborreliosis vary in methodological quality and content. Health care providers and patients need to be aware of this variability in quality when choosing recommendations for their treatment decisions regarding Lyme neuroborreliosis. No statement can be given on quality of content and validity of recommendations, as these issues are not subject to assessment with the AGREE II tool and are prone to individual interpretation of the available evidence by the corresponding guideline panels. To enhance guideline quality, guideline panels should put more emphasis on linking recommendations to the available evidence, transparency in reporting how evidence was searched for and evaluated, and the implementation of recommendations into clinical practice.